A simple sonographic approach to thoracic transforaminal epidural injections for zoster-associated pain involving multiple nerves: an exploratory prospective cohort study - Shuyue Zheng; Dan Wang; Li Yue; Liangliang He (Korean Journal of Anesthesiology)
Background A simple superoposterior approach to thoracic transforaminal epidural injections (TFEIs) under ultrasonographic guidance was proposed to reduce zoster-associated pain (ZAP) involving multiple thoracic nerves and the likelihood of transitioning to postherpetic neuralgia (PHN). Methods Patients were prospectively enrolled. Primary endpoints were the burden of illness (BOI) scores and epidural contrast spread. Secondary endpoints included number of needle insertion attempts, sensory blockade, hemodynamic changes, procedure time, radiation dose, adverse events, rescue analgesics, PHN incidence and EuroQoL 5-Dimension scores. Results Thirty-five injections were performed in 27 patients. Median levels of cephalad-caudad epidural contrast spread were 3, 4, and 5 ml following injections of 2, 3, and 4 ml. Dorsal epidural spread was observed at levels 3, 4, and 5, whereas concurrent ventral spread was observed at levels 2, 3, and 4. BOI scores at 30–180 days significantly decreased (mean difference: −25.3, 95% CI [−57.4 to 6.6], P = 0.005), accounting for reduced rescue analgesic requirements and PHN occurrence and improved EuroQoL 5-Dimension scores. Median sensory blockade at 5 min post-procedure was at level 2, 3, and 4 after 2, 3, and 4 ml of therapeutic injectate. No significant hemodynamic changes were noted at 15 min post-injection. No serious adverse events were observed. Conclusions Spread of thoracic epidural contrast to all involved nerves was confirmed using this novel technique. Simplified needle placement reduced the technical difficulty and risk of complications. It might be a promising alternative approach for ZAP.